MENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN METODE BELAJAR DISCOVERY LEARNING TIPE ROLE PLAYING PADA PEMBELAJARAN PAK KELAS XII DI SMAK SANTO MIKHAEL SOLOR - Krisantus Kenato; Alfonsus Mudi Aran (CV. Adiba Aisha Amira, 2026)
This study aimed to improve students’ learning outcomes through the implementation of the Discovery Learning model with the Role Playing approach in Catholic Religious Education on the topic of Evangelization Mission and Pentecost for Grade XII students at SMAK Santo Mikhael Solor. The study was motivated by low student achievement, limited active participation, and teacher-centered learning practices. This research employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The subjects of this study were 16 Grade XII students. Data were collected through observation, documentation, and learning achievement tests. The data were analyzed using descriptive quantitative and qualitative methods. The results showed that the implementation of the Discovery Learning model with the Role Playing approach significantly improved students’ learning outcomes and classroom participation. In Cycle I, the average student score was 58.9 with a learning mastery percentage of 18.75%. After improvements were made in Cycle II, the average score increased to 89.6 with a mastery percentage of 100%. In addition, students’ participation and learning activities also improved, as seen in their confidence in discussions, role-playing activities, expressing opinions, and connecting Gospel values with daily life. Based on the findings, it can be concluded that the Discovery Learning model with the Role Playing approach is effective in improving learning outcomes, student participation, and the quality of Catholic Religious Education learning processes for Grade XII students at SMAK Santo Mikhael Solor.